1984
DOI: 10.1121/1.390558
|View full text |Cite
|
Sign up to set email alerts
|

Temporal integration of forward masking in listeners having sensorineural hearing loss

Abstract: Findings are described from three experiments that were designed to contrast estimates of auditory time and frequency analysis in highly practiced, young adult subjects having sensorineural hearing loss of cochlear origin with subjects having normal hearing. In one experiment, pure-tone detection threshold was measured for two durations of tones. For the hearing-impaired subjects, smaller differences were found between thresholds for the two durations of tones than were found for the normally hearing subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 9 publications
6
45
1
1
Order By: Relevance
“…From these findings they concluded that the MOC has only a weak influence on the temporal aspects of masking. As stated earlier, similar small effects of masker duration are present in the literature involving frequency selectivity (e.g., Kidd et al, 1984;Bacon and Jesteadt, 1987). The present study and previous studies using precursors have shown that the MOC may play a large role in temporal masking (Strickland, 2001;Krull and Strickland, 2008;Jennings et al, 2009;Roverud and Strickland, 2010).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…From these findings they concluded that the MOC has only a weak influence on the temporal aspects of masking. As stated earlier, similar small effects of masker duration are present in the literature involving frequency selectivity (e.g., Kidd et al, 1984;Bacon and Jesteadt, 1987). The present study and previous studies using precursors have shown that the MOC may play a large role in temporal masking (Strickland, 2001;Krull and Strickland, 2008;Jennings et al, 2009;Roverud and Strickland, 2010).…”
Section: Discussionsupporting
confidence: 68%
“…In forward masking, where the masker does not suppress the signal, studies comparing estimates of frequency selectivity for short and long maskers have produced similarly mixed results, with one study reporting slightly broader tuning with masker duration (Kidd et al, 1984) and another reporting sharper tuning (Bacon and Jesteadt, 1987). Based on the assumption that the MOC reflex plays a role in the dynamics of frequency selectivity, it may be difficult to observe a large change in tuning between short and long maskers.…”
Section: Introductionmentioning
confidence: 92%
“…The findings that the prescriptive procedure and compression speed affect forward masking are consistent with previous research on forward masking. When differences in audibility are minimized between the two groups (NH and SNHL) disparities in forward masking are reduced (Kidd et al, 1985;Schairer et al, 2008). Desloge et al (2011) demonstrated that mimicking the loss of audibility and cochlear compression in the impaired ear using listeners with NH reduced differences in forward masking relative to listeners with SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3), it is plausible that percepts such as forward masking could also be disrupted. For example, subjects with hearing loss exhibit greater forward masking (Kidd et al, 1984;Gagne, 1988), making it harder to detect soft signals in a noisy environment.…”
Section: Hearing Loss Perturbs Temporal Precisionmentioning
confidence: 99%